2020
DOI: 10.21203/rs.3.rs-90384/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migration among Farmers in Delta State, Nigeria: Is it a Climate Change Adaptation Strategy?

Abstract: Objective: The study has the purpose of evaluating the nexus between climate change and migration of farmers in Delta State, Nigeria. The influence exerted by cognitive situations and climate – driven stress on farmers’ decisions to migrate and the socioeconomic attributes of migrating and non-migrating farm families are examined. The emphasis is the function of migration in accessing climate and agricultural extension services as well as the contribution made by migration to promote farmers’ climate change co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Examined the herdsmen and farmers conflicts in North-Eastern Nigeria investigating its causes, repercussions and resolutions [55]. The study described the traditional relationship between Fulani herdsmen and farmers within the purview of incessant resource conflicts observed in Yoba State and how it affected livelihood security of those involved and resource sustainability for the local communities.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Examined the herdsmen and farmers conflicts in North-Eastern Nigeria investigating its causes, repercussions and resolutions [55]. The study described the traditional relationship between Fulani herdsmen and farmers within the purview of incessant resource conflicts observed in Yoba State and how it affected livelihood security of those involved and resource sustainability for the local communities.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The study results showed that factors associated with HIV viral load include: social isolation, multiple late appointments in the previous year, not on a single tablet regimen, high-internalized HIV stigma and immunological treatment failure, while Age (<35years), and fear of disclosure demonstrated a trend toward associations with unsuppressed viral load. Ofuoku (2017), while examining HIV/AIDs awareness and communication methods among students in Delta Central Senatorial district, Delta State, Nigeria, showed that there was significant difference in the awareness level of male and female students on causes and means of transmitting HIV/AIDs infection; there was no significant difference in the awareness level of preventive measures in either urban or rural areas. Adejumo et al (2020) used multivariate analysis techniques to identify the factors associated with HIV infection and knowledge of HIV.A total of 4,273 clients were screened for HIV within the study period.…”
Section: Introductionmentioning
confidence: 96%